Bone cutting capacity and osseointegration of surface-treated orthodontic mini-implants - Kim, Ho-Young (Korean J Orthod, 2016)
OBJECTIVE: The objective of the study was to evaluate the practicality and the validity of different surface treatments of self-drilling orthodontic mini-implants (OMIs) by comparing bone cutting capacity and osseointegration. METHODS: Self-drilling OMIs were surface-treated in three ways: Acid etched (Etched), resorbable blasting media (RBM), partially resorbabla balsting media (Hybrid). We compared the bone cutting capacity by measuring insertion depths into artificial bone (polyurethane foam). To compare osseointegration, OMIs were placed in the tibia of 25 rabbits and the removal torque value was measured at 1, 2, 4, and 8 weeks after placement. The specimens were analyzed by optical microscopy, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS). RESULTS: The bone cutting capacity of the etched and hybrid group was lower than the machined (control) group, and was most inhibited in the RBM group (p < 0.05). At 4 weeks, the removal torque in the machined group was significantly decreased (p < 0.05), but was increased in the etched group (p < 0.05). In the hybrid group, the removal torque significantly increased at 2 weeks, and was the highest among all measured values at 8 weeks (p < 0.05). The infiltration of bone-like tissue surface was evaluated by SEM, and calcium and phosphorus were detected via EDS only in the hybrid group. CONCLUSIONS: Partial RBM surface treatment (hybrid type in this study) produced the most stable self-drilling OMIs, without a corresponding reduction in bone cutting capacity.